Bound states and symmetry breaking of the ring C-20(-) anion - Yang, Yi-Fan; Cederbaum, Lorenz S. (The journal of chemical physics, 2020)
Determining the geometry of carbon rings is an ongoing challenge. Based on our calculations at a state-of-the-art level, we found that the C-20(-) ring possesses five bound electronic states, including a superatomic state, which is the first superatomic state found for a ring. The nature of these electronic states is discussed. Our calculation reveals a symmetry breaking of the C-20(-) ring anion ground electronic structure occurring upon attaching an electron to the neutral ring. The discussion of the possible symmetry breaking mechanisms indicates that the shrinking and distortion of the ring upon electron attachment, leading to the symmetry breaking, is a result of the interplay between the symmetry breaking and the totally symmetric modes. The discussion enriches the palette of possible symmetry breaking phenomena in carbon clusters.
Gesehen am 24.07.2020
Im Titel erscheint die Zahl 20 tiefgestellt und das Minus-Zeichen hochgestellt